Analysis of hunting statistics collection frameworks for wild boar across Europe and proposals for improving the harmonisation of data collection. Issue 12 (13th December 2018) - Consortium, ENETwild; Vicente, Joaquín; Plhal, Radim; Blanco‐Aguiar, Jose A; Sange, Marie; Podgórski, Tomasz; Petrovic, Karolina; Scandura, Massimo; Nabeiro, Anna Cohen; Body, Guillaume; Keuling, Oliver; Apollonio, Marco; et al.
Abstract : Heterogeneities in the wild boar data collection frameworks across Europe were analysed using questionnaires to explore comparability of hunting data in the short term and propose a common framework for future collection. Fifty‐seven respondents representing 32 countries covering more than 95% of European territory participated to the questionnaire. The most frequently recorded information in the official statistics included the quantity of animals shot per hunting ground and season (24 countries) and the size of the hunting (management) ground (21 countries). Georeferenced maps for the hunting grounds were collected (total or partial) for 20 countries. The least frequently recorded information was at the level of hunting events. We conclude that (i) sources of hunting statistics providing quantitative information on wild boar (and by extension, for other big game species) are lacking or are not harmonised across Europe, as well as incomplete, dispersed and difficult to compare; (ii) a feasible effort is needed to achieve harmonisation of data in a short time for the most basic statistics at the hunting ground level, and (iii) the coordination of the collection of hunting statistics must be achieved first at national and then at European level. The following is recommended: (i) countries should collect data at hunting ground level; (ii) efforts should be focused on data‐poor countries (e.g. Eastern Europe), and (iii) the data should be collected at the finest spatial and temporal resolution, i.e. at hunting event level. ENETWILD proposes the development of a robust and well‐informed data collection model as the basis for a common data collection framework. The present report identified some countries where, though the potential to share good quality data is present, the data collection promoted by ENETWILD has not succeeded so far (i. e. Eastern Europe). This highlights the need of further strategies to be developed so to encourage and support these countries to share hunting data.